XXII Balcanicum, Memory places and politics of memory in The South-East Europe, Poznań, October 20th-21st, 2023. Conference report - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2023)
The XXII Balcanicum conference was held on October 20-21, 2023, organized by the Commission on Balkan Studies, in cooperation with the Faculty of History of the Adam Mickiewicz University. The theme of this year's scientific session was formulated as follows: Memorial places and politics of memory in the South-East Europe. 33 presented papers reflected various aspects of the phenomenon of commemoration of characters, processes, historical events defining real and symbolic spaces in the South-East Europe, in the past and today. The participants presented various approaches on such issueas as the place and role of politics of memory in the functioning of societies, regional and local communities, families and individuals. Moreover, they discussed the use and perception of various instruments of the politics of memory (as for scientific research, institutional aspect, legislation, monumental or toponymic landscape, education, media e.t.c.) and their impact on public discources about the past.